Development of Snakes and Ladders Media Based on QR Code Material on the Value of the Pancasila Precepts with the Character of love for the Country in Grade V Elementary School - Aslafi, Iqbal Darul; Ahdhianto, Erif; Barus, Yohannes Kurniawan (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2024)
The purpose of research and development is to develop learning media for snakes and ladders based on QR Code material on the values of the Pancasila precepts with valid, practical and effective contents of love for the homeland for class V SD. This development uses the Research and Development (RD) method by following the Analize, Design, Development, Implementation, and Evaluation (ADDIE) steps. This research uses a type of pre-experimental research using one group pretest-posttest design. Collecting data using interviews, questionnaires and tests of student learning outcomes. This study involved 2 experts, one teacher, and 21 students. Material expert validation gets 88.2% results, media experts get 98.6% results, users get 100%. The practicality of the product by students and teachers obtained a result of 100% and the effectiveness of the product showed that there were differences before being given treatment and after being given treatment in the form of snakes and ladders media. This can be seen by using Paired Sample T Test with significance value of 0.000 less than 0.05. The conclusion of this study is snakes and ladders learning media based on QR Code, material for the values of Pancasila precepts with love for the motherland character content for class V SD, according to the validator, very valid, practical for students and teachers, and effective in learning